Ayurvedic Management of Eosinophilic Esophagitis (EOE): A Comprehensive Case Study from Australia (International Journal of Ayurveda and Pharma Research, 2025)
This paper presents a structured case study of an EoE patient treated with individualized Ayurvedic protocols at the Institute of Applied Food Allergy® (IAFA). The results demonstrate significant symptomatic relief, improved eosinophil profiles, and normalization of associated conditions. The Ayurvedic approach included Agnideepana, Ama Pachana, Dosha Pratyaniak Chikitsa, and Rasayana therapy, supported by dietary and lifestyle guidance. Objective: To document and evaluate the outcomes of individualized Ayurvedic management of biopsy-confirmed EoE patients at the Institute of Applied Food Allergy (IAFA), focusing on symptom regression, immunological moderation, digestive correction, and overall quality of life. Methods: A longitudinal observational case study was conducted. Clinical presentation, endoscopic and hematologic parameters, food allergy testing, and quality of life were documented. The Ayurvedic diagnosis corresponded with Amlapitta (acid reflux disorder) and Rikshajivha (Tinea Versicolor). Treatment included herbal formulations like Aahar Amrutham Ras, Pitpapra Capsules, Triphala, etc., along with dietary regulation and topical applications. The patient was concurrently on Budesonide and proton-pump inhibitors (PPI). Results: Over one year, the patient demonstrated progressive clinical resolution, including normalization of eosinophil counts, improvement in food tolerance, and endoscopic evidence of complete esophageal healing by October 2024. No relapse was reported by the September 2025 follow-up. Conclusion: This case supports the integrative role of Ayurvedic principles in managing EoE by addressing gut immunity, systemic inflammation, and allergen sensitivity, offering a viable adjunctive approach alongside modern therapies.